"I never imagined" pronunciation as "such an interesting thing": Student teacher perception of innovative practices. (18th January 2019) - Burri, Michael; Baker, Amanda
Abstract : Despite extensive research conducted into language teacher education practices and outcomes, student teachers' uptake of innovative practices is still largely unexplored. This study examined the perception of 15 graduate student teachers of a unique haptic (movement and touch) pronunciation teaching method in which they were trained. Focus group interviews, semi‐structured interviews, and weekly observations were triangulated over a period of 16 weeks to attain insights into participants' perceptions of haptic pronunciation teaching. Findings suggested that their overall view of haptic pronunciation instruction was positive, but challenges with performing the pedagogical movements and uncertainty about the method's efficacy clouded some of their perceptions. The paper concludes with a discussion about supporting student teachers in overcoming their doubts about applying innovative pedagogy.